Local Union Officers' Donations to a Political Action Committee - Masters, Marick; Atkin, Robert (Relations industrielles / Industrial Relations, 1996)
During the 1980s, unions in the United States significantly increased their political activity, partly as a strategic response to declining membership. An important aspect of this effort is contributing money to congressional and presidential candidates through political action committees (PACs). U.S. federal election campaign laws allow unions to raise PAC money from members on a strictly uoluntary basis. Elected local union officers may play an important part in union PAC fundraising, as they are a sizable cadre of potential donors and their donations may send powerful signais to rank-and-file to donate as well. This paper examines the PAC donations among a sample of elected local union officers of the United Steelworkers of America (USW). The descriptive results show significant variation in officers' PAC donations. Regression analyses show that union commitment is a significant predictor of PAC support as is location in a non-right-to-work state. The results have implications for promoting union PAC fundraising efforts, and hence the potential of U.S. unions to rely on political action as a strategy for resurgence.